Development of a quantitative method for the simultaneous analysis of the boar taint compounds androstenone, skatole and indole in porcine serum and plasma by means of ultra-high performance liquid chromatography coupled to high resolution mass spectrometry. (15th November 2015) - Wauters, J.; Vanden Bussche, J.; Verplanken, K.; Bekaert, K.M.; Aluwé, M.; Van den Broeke, A.; Coussé, A.; Buys, N.; Vanhaecke, L.
Highlights: First serum and plasma analysis for the three boar taint compounds simultaneously. Optimized and validated UHPLC-HR-Orbitrap-MS method. Fast, specific and sensitive quantification of indole, skatole and androstenone. Reliable correlation assessment between blood and fat thanks to method-alignment. Novel tool to evaluate entire boar-raising strategies as alternative for castration. Abstract: Boar taint is an off-odour occurring while heating meat or fat from boars. A method detecting the three compounds (androstenone, skatole and indole) simultaneously in blood would offer substantial advantages since it would allow monitoring the impact of rearing strategies. Therefore, a UHPLC-HR-Orbitrap-MS analysis method is optimized and validated for the quantification of these compounds in plasma or serum. Sample pre-treatment involved an extraction with diethylether followed by a centrifugal filtration (30 kDa). Limits of detection and quantification varied between 0.5 and 1 μg L −1 and 2 and 3 μg L −1 for the three compounds, respectively. Besides, an excellent repeatability (RSD < 7.6%), within-laboratory reproducibility (RSD < 10.5%), recovery (87–97%) and linearity ( R 2  > 0.99) were recorded. Correlations between serum/plasma and fat levels of the boar taint compounds were positive for skatole ( r serum  = 0.39 and r plasma  = 0.84) and androstenone ( r serum  = 0.73–0.78 and r plasma  = 0.32–0.80).